Direct enantioselective reduction of C=C bond of β-polyfluoro-alkylated enones via asymmetric photoredox catalysis - Zhang, Linghong; Ma, Jin; Ban, Xu; Zhao, Xiaowei; Yin, Yanli; Jiang, Zhiyong (Science China. Chemistry, 2024)
Direct enantioselective reduction of the C=C bond of β-polyfluoro-alkylated enones is an important but long-pending subject in asymmetric catalysis. Here, we report on the viability of visible light-driven cooperative photoredox and chiral hydrogen-bonding catalysis to effectively address this challenge, as a variety of products are obtained in high yields (up to 85%) with good to excellent enantioselectivities (up to 98% ee). The formation of thermodynamically favorable enol intermediates after double single-electron reduction represents the center of the success. Additionally, the utility of the current method is validated by the convenient regio-specific and -diverse synthesis of various deuterated derivatives for these products using inexpensive D 2 O as the deuterium source.